Denture Labeling Using QR Codes. A Simplified Technique - Jiménez DDS, Rodrigo A. (Odovtos - International Journal of Dental Sciences, 2018)
Denture identification procedures have multiple benefits for denture wearers. These include prevention of losing or misplacing dentures and forensic identification of victims. A simplified inclusion technique is fully described to label dentures with QR code prints.